1993
DOI: 10.1161/01.atv.13.6.771
|View full text |Cite
|
Sign up to set email alerts
|

Decreased basal nitric oxide release in hypercholesterolemia increases neutrophil adherence to rabbit coronary artery endothelium.

Abstract: Hypercholesterolemia, before atherosclerosis, is known to reduce agonist-(e.g., acetylcholine) mediated nitric oxide (NO) production within 2 weeks of a cholesterol-enriched diet. However, no data exist on the effect of hypercholesterolemia on the basal release of NO from blood vessels. We studied the basal release of NO in rabbit coronary arteries by addition of the NO synthase blocker yV G -nltro-L-arginine-methyl ester (L-NAME). Basal release of NO was markedly attenuated 2 weeks after introduction of a 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
56
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(61 citation statements)
references
References 35 publications
4
56
0
1
Order By: Relevance
“…Therefore, our present results suggest that early inflammatory and proliferative changes play a key role in the development of subsequent structural changes observed during late phases in this model. Although a short-term reduction in NO synthesis has been shown to increase neutrophil rolling and adherence to the endothelium, 32,33 no such polymorphonuclear cells was observed in the lesions.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, our present results suggest that early inflammatory and proliferative changes play a key role in the development of subsequent structural changes observed during late phases in this model. Although a short-term reduction in NO synthesis has been shown to increase neutrophil rolling and adherence to the endothelium, 32,33 no such polymorphonuclear cells was observed in the lesions.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, it is likely that this endothelial dysfunction will result in increased adherence of other blood cell elements, such as neutrophils and platelets. 25,26 Furthermore, these risk factors may also have important direct effects on circulating cells to enhance their activity. Indeed, we have previously observed that mononuclear cells isolated from patients with non-insulin-dependent diabetes mellitus bind more avidly to cultured ECs than do mononuclear cells derived from control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Inhaled nitric oxide gas reverses pulmonary hypertension (27), reverses pulmonary vasoconstriction (28), improves lung function in affected patients and increases ventilation-perfusion ratios (29). In addition, nitric oxide inhibits platelet aggregation (13 -15), platelet (30,31) and leukocyte (16)(17)(18) adhesion on endothelial cells and vascular albumin leakage (19,20). Thus, nitric oxide seems to contribute greatly to maintaining physiological functions in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelium releases numerous biologically important materials, one of which is endothelium-derived relaxing factor (EDRF): nitric oxide (8) or nitrosothiol (9)(10)(11). EDRF released from vascular endothelial cells plays an important role in cardiovascular and pulmonary systems, being involved in vasodilation (12), inhibition of platelet aggregation (13 -15), leukocyte adhesion (16)(17)(18) and vascular albumin leakage (19,20). Although DEP is thought to be a causative factor responsible for the recent increase in patients with pulmonary diseases, neither the cause-and-result relationship nor the pathogenic mechanism has been demonstrated.…”
mentioning
confidence: 99%